(untitled) (Dhaka University Journal of Biological Sciences, 2019)
An incubation study was conducted to find out the best mixing ratio of acid and calcareous soil (maintaining 70% moisture) for pot experiment. Depending on various physico-chemical properties mixed soil 1 : 1 (i.e. acid : calcareous) was selected for pot experiment. The pot experiment was carried out to observe the effects of vermicompost and compost on soil properties and growth and yield of Kalmi (Ipomoea aquatica Forsk.). This experiment included seven treatments with three replications including control. Treatment variables were T0 (control), T1 (4 t/ha vermicompost), T2 (8 t/ha vermicompost), T3 (12 t/ha vermicompost), T4 (4 t/ha compost), T5 (8 t/ha compost) and T6 (12 t/ha compost). All the treatments had significant positive effects over control on growth and yield of kalmi. The highest growth and yield were recorded with T3 (12 t/ha vermicompost) treatment. In case of, macro and micronutrient uptake treatment T3 (12 t/ha vermicompost) performed best followed by T6 (12 t/ha compost) over T0 (control). However, in post-harvest soil except soil reaction (pH); electrical conductivity (EC), organic carbon (OC), available N, P, K, S, Ca, Mg, Na, Fe and Zn significantly increased for T3 (12 t ha-1 vermicompost) than T1, T2, T4, T5, T6 and T0. Dhaka Univ. J. Biol. Sci. 28(1): 121-129, 2019 (January)